2003
DOI: 10.1046/j.1365-8711.2003.06202.x
|View full text |Cite
|
Sign up to set email alerts
|

Gaussianity of cosmic velocity fields and linearity of the velocity--gravity relation

Abstract: We present a numerical study of the relation between the cosmic peculiar velocity field and the gravitational acceleration field. We show that on mildly non‐linear scales (4–10 h−1 Mpc Gaussian smoothing), the distribution of the Cartesian coordinates of each of these fields is well approximated by a Gaussian. In particular, their kurtoses and negentropies are small compared to those of the velocity divergence and density fields. We find that at these scales the relation between the velocity and gravity field … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…It is commonly approximated by a multivariate Gaussian (Strauss et al 1992, hereafter S92; Schmoldt et al 1999, hereafter S99). This approximation has support from numerical simulations (Kofman et al 1994; Cieciela̧g et al 2003), where the measured non‐Gaussianity of g and v is small. This is rather natural to expect since, for example, gravity is an integral of density over effectively a large volume, so the central limit theorem can at least partly be applicable (but see Catelan & Moscardini 1994).…”
Section: Analytical Description Of the Likelihoodsupporting
confidence: 53%
“…It is commonly approximated by a multivariate Gaussian (Strauss et al 1992, hereafter S92; Schmoldt et al 1999, hereafter S99). This approximation has support from numerical simulations (Kofman et al 1994; Cieciela̧g et al 2003), where the measured non‐Gaussianity of g and v is small. This is rather natural to expect since, for example, gravity is an integral of density over effectively a large volume, so the central limit theorem can at least partly be applicable (but see Catelan & Moscardini 1994).…”
Section: Analytical Description Of the Likelihoodsupporting
confidence: 53%
“…In this section we perform controlled numerical experiments to test the velocity–gravity relation, both in real and redshift space, on the dark matter distribution. These analyses extend the work of Cieciela̧g et al (2003) who performed similar work but only in real space and on simulations using a pure hydrodynamic code approximating the dynamics of dark matter, namely the Cosmological Pressureless Parabolic Advection code of Kudlicki, Plewa & Różyczka (1996, see also Kudlicki et al 2000).…”
Section: Numerical Experimentssupporting
confidence: 60%
“…Furthermore, since the low‐ v regime converges to linear theory, all the curves corresponding to superpose in that regime, creating a ‘caustic’ of best likelihood nearby the maximum of the joint PDF, explaining the very good agreement with linear expectation in that region. As a result, we now understand, thanks to the spherical top‐hat model, both the ‘propeller’ shape of the bivariate PDF, as well as the remarkable agreement with linear theory prediction nearby its maximum, even in the highly non‐linear regime (see also Cieciela̧g et al 2003). The arguments developed here are oversimplified, but capture the main features of the dynamics of the large‐scale structures prior to shell crossing in real space.…”
Section: Numerical Experimentsmentioning
confidence: 53%
See 1 more Smart Citation
“…These two quantities are highly linear. It has been directly shown for velocity fields by Ciecielg et al (2003) and indirectly shown by Mohayaee et al (2006) and Lavaux et al (2008a) for the displacement field. This linearity helps us at constructing an analytical statistical model of the voids.…”
Section: Comparison Of Diva To Earlier Void Findersmentioning
confidence: 94%